Organizational Legitimacy Strategy Through Privatization, Edtech, and Data Systems: A Study at An-Nahl High School in Jambi - Mukhtar Latif; Jamrizal Jamrizal; Muhammad Zaki Rahman; Nispi Syahbani (Journal of Educational Sciences, 2026)
The contemporary landscape of Islamic education is characterized by increasing legitimacy pressures, encompassing regulatory, normative, and cognitive dimensions. Islamic educational institutions are required to respond to modernization and market competition while maintaining their Islamic identity. This study aims to examine organizational legitimacy strategies implemented by SMA IT An-Nahl Jambi through the integration of privatization, educational technology (EdTech), and data management systems. This research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews with key informants, and document analysis, and were analyzed using the interactive data analysis model proposed by Miles, Huberman, and Saldaña. The findings indicate that privatization provides managerial autonomy that enables curricular innovation and service differentiation, thereby strengthening regulatory and normative legitimacy. The adoption of EdTech functions as a cognitive legitimacy strategy by projecting the image of an Islamic school that is modern, adaptive, and responsive to digital-era demands. Furthermore, data systems and information management enhance transparency, accountability, and evidence-based decision-making, contributing to stronger regulatory and normative legitimacy. This study concludes that sustainable organizational legitimacy in Islamic education cannot be achieved through isolated strategies but requires an integrated approach combining privatization, EdTech, and data systems within a coherent educational management ecosystem grounded in Islamic values.